Impulsivity, gender, and the platelet serotonin transporter in healthy subjects - Donatella Marazziti (Dove Medical Press, 2009)
Donatella Marazziti, Stefano Baroni, Irene Masala, Francesca Golia, Giorgio Consoli, Gabriele Massimetti, Michela Picchetti, Mario Catena Dell’Osso, Gino Giannaccini, Laura Betti, Antonio Lucacchini, Antonio CiapparelliDipartimento di Psichiatria, Neurobiologia, Farmacologia e Biotecnologie, University of Pisa, Pisa, ItalyAbstract: The present study explored the possible relationships between impulsivity, gender, and a peripheral serotonergic marker, the platelet serotonin (5-HT) transporter (SERT), in a group of 32 healthy subjects. The impulsivity was measured by means of the Barratt Impulsivity Scale, version 11 (BIS-11), a widely used self-report questionnaire, and the platelet SERT was evaluated by means of the specific binding of 3H-paroxetine (3H-Par) to platelet membranes, according to standardized protocols. The results showed that women had a higher BIS-11 total score than men, and also higher scores of two factors of the same scale: the motor impulsivity and the cognitive complexity. The analysis of the correlations revealed that the density of the SERT proteins, as measured by the maximum binding capacity (Bmax) of 3H-Par, was significantly and positively related to the cognitive complexity factor, but only in men. Men showed also a significant and negative correlation with the dissociation constant, Kd, of (3H-Par) binding, and the motor impulsivity factor. These findings suggest that women are generally more impulsive than men, but that the 5-HT system is more involved in the impulsivity of men than in that of women.Keywords: impulsivity, gender, serotonin transporter, Barratt Impulsivity Scale, platelets, 3H-paroxetine